An immediate bone remodeling response is necessary to prevent second metatarsal stress fractures in runners - Edwards, W. B.; Miller, R. H. (International Calgary Running Symposium, August 14-17, 2014, 2014)
Repetitive bone loading leads to microdamage accumulation that may result in failure (i.e., stress fracture) without an adequate remodelling response. Although the second metatarsal (Met-2) experiences large bending loads during the push-off phase of running, the rate of Met-2 stress fractures is fairly low. Thus, remodelling may play a critical role in the prevention of Met-2 injury, and understanding the fatigue-life of Met-2 during running may elucidate this phenomenon. Our purpose was to quantify the loading cycles (NF) and running distance (dF) until Met-2 failure in the absence of remodelling. A theoretical model was used to predict Met-2 failure for a 170 cm, 69 kg male running at 2-6 m/s. The relationship among running speed, stride length (SL), and ground reaction force (GRF) was estimated from the literature. Peak Met-2 stress was predicted using the finite element method (Fig 1), assuming the applied force was 24% of the GRF based on insole pressure data. The relationship between peak stress and NF was determined using empirical relationships from in vitro fatigue studies, and dF=(NF)(SL). The stress experienced by Met-2 during running was associated with a NF of 6,922-50,374 cycles and dF of 27.9-88.2 km, depending on speed (Table 1). Even the recreational runner could bank this distance in a few months or perhaps weeks of training. Given an estimated remodeling cycle - activation, resorption, and formation - of 12 weeks, and the relatively low incidence of Met-2 stress fractures in runners, we propose an immediate remodelling response must occur to repair bone microdamage.